Developing cultural humility in an international social work classroom. Issue 5 (4th July 2022) - Harindranathan, Priya; Addo, Reuben; Koers, Gregory; Parra-Perez, Lizeth Guadalupe
ABSTRACT: It is important that social work students engage in critical reflection of curriculum content in the classroom as a prerequisite for developing cultural humility to engage in unbiased cross-cultural professional practice. The present study explored students' learning, centered on cultural humility, among predominantly White students enrolled in an international social work course in a U.S. university. Participant observation, focus groups, and in-depth interviews were used to explore students' reflections. Results indicate that the participants recognized their privilege and barriers to understanding different cultures, were open to alternate models of development from other cultures, and expressed a willingness to understand and empathize with cultures different from their own. These findings underline the need to integrate international content in the social work curriculum using multiple pedagogical strategies and to provide students opportunities for critical self-reflection in classrooms.